A ANALISIS PENGARUH PEMBANGUNAN PASAR SANGGAM AJI DILAYAS TERHADAP SOSIAL EKONOMI MASYARAKAT DI KELURAHAN GUNUNG TABUR KABUPATEN BERAU - Hakim, Abdul (ECO-BUILD, 2017)
Analysis of the Influence of Market Development Sanggam Aji Dilayas Against Socio Economic Community in Gunung Tabur Village, Berau District. The purpose of this study is To obtain information on the Influence of Market Development Sanggam Adji Dilayas Against Social Economic Society in Guung Tabur Village Berau District. Based on the results of research with empirical rs -1,503 <0.423, then the research hypothesis is rejected, in other words the development of the Sanggam Aji Dilayas market is not affect the socio-economic improvement of the community of Gunung Tabur